2003
DOI: 10.1034/j.1600-6143.2003.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Linked Immunosorbent Spot (ELISPOT) Assay for Interferon‐Gamma Independently Predicts Renal Function in Kidney Transplant Recipients

Abstract: Post-transplant monitoring of cellular immunity might be useful in predicting long-term outcomes of kidney transplant recipients. We used an enzyme linked immunoabsorbent spot (ELISPOT) assay to serially measure the frequency of peripheral blood lymphocytes producing interferon-gamma in response to stimulator cells from donors or third parties in 55 primary kidney transplant recipients. Mean frequencies measured during the first 6 months after transplantation correlated significantly with the serum creatinine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(126 citation statements)
references
References 26 publications
7
114
1
4
Order By: Relevance
“…In addition, the assay has been optimized for use of frozen cells that can be easily stored. Although no studies to date have reported the use of this assay to identify functionally tolerant humans after transplantation, the frequency of IFN-␥-producing cells has been reported to correlate with the incidence of acute and chronic rejection as well as allograft function after renal transplantation (45)(46)(47). Obtaining and storing sufficient numbers of donor cells to perform the assay repeatedly is a practical limitation, particularly in recipients of deceased-donor organs.…”
Section: Elispot Assaymentioning
confidence: 99%
“…In addition, the assay has been optimized for use of frozen cells that can be easily stored. Although no studies to date have reported the use of this assay to identify functionally tolerant humans after transplantation, the frequency of IFN-␥-producing cells has been reported to correlate with the incidence of acute and chronic rejection as well as allograft function after renal transplantation (45)(46)(47). Obtaining and storing sufficient numbers of donor cells to perform the assay repeatedly is a practical limitation, particularly in recipients of deceased-donor organs.…”
Section: Elispot Assaymentioning
confidence: 99%
“…Certainly, the donorspecific immune evaluation is feasible nowadays; on one hand, donorspecific alloantibodies can be precisely monitored by flow cytometric, cytotoxicity, or ELISA crossmatching techniques, and on the other, high frequency of donor-specific alloreactive T cells can be evaluated by the ELISPOT assay. Indeed, these procedures have been shown to be useful for predicting graft outcome (27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Measurements of mitogen-stimulated ATP production by T-lymphocytes, and of immunoreactive Tcells by techniques such as the ELISPOT assay or flow cytometry, can better educate and inform the clinician confronting the unique treatment dilemma presented by this patient. 9,10 Rakesh Sindhi, MD, FACS Hillman Center for Pediatric Transplantation Children's Hospital of Pittsburgh Pittsburgh, PA…”
Section: To the Editorsmentioning
confidence: 99%